Potential Effect and Analysis of High Residential Solar Photovoltaic (PV) Systems Penetration to an Electric Distribution Utility (DU) - Jeffrey Tamba Dellosa (International Journal of Renewable Energy Development, 2016)
The Renewable Energy Act of 2008 in the Philippines provided an impetus for residential owners to explore solar PV installations at their own rooftops through the Net-Metering policy. The Net-Metering implementation through the law however presented some concerns with inexperienced electric DU on the potential effect of high residential solar PV system installations. It was not known how a high degree of solar integration to the grid can possibly affect the operations of the electric DU in terms of energy load management. The primary objective of this study was to help the local electric DU in the analysis of the potential effect of high residential solar PV system penetration to the supply and demand load profile in an electric distribution utility (DU) grid in the province of Agusan del Norte, Philippines. The energy consumption profiles in the year 2015 were obtained from the electric DU operating in the area. An average daily energy demand load profile was obtained from 0-hr to the 24th hour of the day based from the figures provided by the electric DU. The assessment part of the potential effect of high solar PV system integration assumed four potential total capacities from 10 Mega Watts (MW) to 40 MW generated by all subscribers in the area under study at a 10 MW interval. The effect of these capacities were measured and analyzed with respect to the average daily load profile of the DU. Results of this study showed that a combined installations beyond 20 MWp coming from all subscribers is not viable for the local electric DU based on their current energy demand or load profile. Based from the results obtained, the electric DU can make better decisions in the management of high capacity penetration of solar PV systems in the future, including investment in storage systems when extra capacities are generated.Article History: Received July 15th 2016; Received in revised form Sept 23rd 2016; Accepted Oct 1st 2016; Available onlineHow to Cite This Article: Dellosa, J. (2016) Potential Effect and Analysis of High Residential Solar Photovoltaic (PV) Systems Penetration to an Electric Distribution Utility (DU). Int. Journal of Renewable Energy Development, 5(3), 179-185.http://dx.doi.org/10.14710/ijred.5.3.179-185